The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.compstruct.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid micromechanical-phenomenological modelling of anisotropic damage and anelasticity induced by micro-cracks in unidirectional composites

Abstract: Fodil Meraghni. Hybrid micromechanicalphenomenological modelling of anisotropic damage and anelasticity induced by micro-cracks in unidirectional composites.Composite Structures, Elsevier, 2017, 182, pp.223-236. 10.1016/j.compstruct.2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…Similar approximation has been considered in Praud et al (2017) and the comparisons with experimental data showed excellent accuracy in the direction parallel to fibers, and quite satisfactory representation of the response normal to the fibers direction. This observation permits to simplify this step of homogenization, by assuming that, only for this case, the matrix also behaves elastically inside the bundle before damage occurs.…”
Section: First Homogenizationmentioning
confidence: 59%
See 4 more Smart Citations
“…Similar approximation has been considered in Praud et al (2017) and the comparisons with experimental data showed excellent accuracy in the direction parallel to fibers, and quite satisfactory representation of the response normal to the fibers direction. This observation permits to simplify this step of homogenization, by assuming that, only for this case, the matrix also behaves elastically inside the bundle before damage occurs.…”
Section: First Homogenizationmentioning
confidence: 59%
“…Damage can appear at the matrix phase, at the interfaces between matrix and fibers or matrix and bundles, or at the fibers themselves. As mentioned in the introduction, this work attempts to integrate damage that is observed at the level of the bundles by using a hybrid phenomenological-micromechanical model, developed by Praud et al (2017). It should be pointed out that the damage model in this work is a "brick" that can be easily interchanged with another damage model.…”
Section: B Bundles Containing Microcracksmentioning
confidence: 99%
See 3 more Smart Citations